THE EFFECT OF TOURISM MOTIVATION ON VISITING DECISIONS IN JAKARTA HISTORY MUSEUM KAWASAN KOTA TUA JAKARTA - Ardiansyah, Imam; Anita, Tiurida Lily (APPS Publications, 2019)
The research at the Jakarta History Museum aims to find out the motivation of tourists consisting of physical motivation, cultural motivation, interpersonal motivation and prestige motivation influencing the decision to visit the Jakarta History Museum. This research includes quantitative research using a descriptive approach. The sample in this study amounted to 100 respondents using the Probability Sampling technique with Simple Random sampling, which is done randomly regardless of the strata in that population. Data analysis techniques use multiple linear regression analysis, classical assumption test, and hypothesis testing. Testing the hypothesis with the t test shows that tourist motivation consisting of physical motivation, cultural motivation, prestige / status motivation has a significant influence on visiting decisions. While the motivation of tourists from interpersonal motivation does not have a significant influence on visiting decisions. From the f test shows the results of tourist motivation variables consisting of physical motivation, cultural motivation, prestige or status motivation together have a significant influence on visiting decisions. While the value of R square is equal to 0.571. This means that tourist motivation only affects the visiting decision of 57.1%. And the rest is influenced by other variables not included in this study. From the results of the study it can be concluded that there is a simultaneous influence on physical motivation, cultural motivation, and status motivation on visiting decisions, whose meaning in that dimension is quite good and needs to be maintained. Whereas in the dimension of interpersonal motivation there is no simultaneous influence on visiting decisions, and it needs to be increased in that dimension.